(3GdGOGQI GdeGdjI GdMOjKI hOQGSGJ GdLOhi GdGbJUGOjIs - (3YdjhI(B, (3GdSjOs ((3GdbGgQIs (3OGQ GdCejfs, 2003)
(3GdGOGQI GdeGdjI GdMOjKI,cja JbQC GdejRGfjI,GdJNWjW, GdeYGOdI GdeMGSHjI,cTa GdMSGH GdNJGej,GdeQGbHI GdOGNdjI deNGRf GdMcheI,OQGSGJ GdLOhi ddeTQhYGJ hGdJj JMJhj eaGgje OQGSI GdLOhi ddeTQhYGJ,OQGSI GdLOhi GdJShjbjI ddeTQhYGJ,OQGSI GdLOhi GdeGdjI ddeTQhYGJ,GdEWGQ GdYGe ddOQGSGJ GdafjI hGdgfOSjI ddeTQhYGJ,Jbjje GdeTQhYGJ HGdeDTQGJ GdEbJUGOjIs
Keywords: (3GdEOGQI GdeGdjIs; (3GdeTQhYGJs; (3GdejRGfjIs; (3OQGSI GdLOhis